2015
DOI: 10.1128/ec.00146-15
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Switching and Biofilm Formation between MTL -Homozygous Strains of Candida albicans and Candida dubliniensis

Abstract: Candida albicans and Candida dubliniensis are highly related species that share the same main developmental programs. In C. albicans, it has been demonstrated that the biofilms formed by strains heterozygous and homozygous at the mating type locus (MTL) differ functionally, but studies rarely identify the MTL configuration. This becomes a particular problem in studies of C. dubliniensis, given that one-third of natural strains are MTL homozygous. For that reason, we have analyzed MTL-homozygous strains of C. d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 68 publications
2
16
0
Order By: Relevance
“…Nobile et al (190) subsequently demonstrated, in a variation of the Douglas model using Spider medium, that the rate of accumulation of budding yeast cells in the medium decreased between 24 and 60 h. It was not clear whether the yeast-phase cells accumulating in the medium originated in the adhesive yeast cell basal layer, were released from the hyphal upper layer, or were released from yeast cell pockets within the hyphal upper region of the developing biofilm. The lowest rate of release was observed in RPMI 1640 (MOPS) medium, which is consistent with the observation that biofilms formed in this medium contain vertically oriented hyphae with few lateral yeast cells (45,183,184). This is therefore consistent with the suggestion that dispersed cells may be formed by hyphae in media that facilitate lateral yeast cell formation.…”
Section: Biofilm Dispersalsupporting
confidence: 78%
See 4 more Smart Citations
“…Nobile et al (190) subsequently demonstrated, in a variation of the Douglas model using Spider medium, that the rate of accumulation of budding yeast cells in the medium decreased between 24 and 60 h. It was not clear whether the yeast-phase cells accumulating in the medium originated in the adhesive yeast cell basal layer, were released from the hyphal upper layer, or were released from yeast cell pockets within the hyphal upper region of the developing biofilm. The lowest rate of release was observed in RPMI 1640 (MOPS) medium, which is consistent with the observation that biofilms formed in this medium contain vertically oriented hyphae with few lateral yeast cells (45,183,184). This is therefore consistent with the suggestion that dispersed cells may be formed by hyphae in media that facilitate lateral yeast cell formation.…”
Section: Biofilm Dispersalsupporting
confidence: 78%
“…In Fig. 4E, a scanning electron micrograph (SEM) is presented from the top of a collapsed 48-h biofilm prepared such that the extracellular matrix was removed (note the homogeneity of hyphae in the top-view image) (45). In Fig.…”
Section: The Douglas Model: a Good Starting Pointmentioning
confidence: 99%
See 3 more Smart Citations